(untitled) (Scientific journal of the Fergana State University, 2023)
Jadid literature, in particular, the work of Cholpon, is one of the masterpieces of our literature. The works written during this period are also important for their ideological strength, perfection of images and consistency of plots. To date, Cholpon, one of the leaders of the Jadid movement, has conducted research on the genre of prose, the structure of stories, and the study of the layers of prose in prose. And this kind of research will enrich our astronomy. This article examines the image of women in Cholpon’s stories.